Use of Composite Protein Database including Search Result Sequences for Mass Spectrometric Analysis of Cell Secretome - Shin, Jihye; Kim, Gamin; Kabir, Mohammad Humayun; Park, Seong Jun; Lee, Seoung Taek; Lee, Cheolju (PUBLIC LIBRARY SCIENCE, 2015)
Mass spectrometric (MS) data of human cell secretomes are usually run through the conventional human database for identification. However, the search may result in false identifications due to contamination of the secretome with fetal bovine serum (FBS) proteins. To overcome this challenge, here we provide a composite protein database including human as well as 199 FBS protein sequences for MS data search of human cell secretomes. Searching against the human-FBS database returned more reliable results with fewer false-positive and false-negative identifications compared to using either a human only database or a human-bovine database. Furthermore, the improved results validated our strategy without complex experiments like SILAC. We expect our strategy to improve the accuracy of human secreted protein identification and to also add value for general use.
Keywords: SHOTGUN PROTEOMICS; SERUM; IDENTIFICATIONS; SENSITIVITY